California Advocate Newspaper's Drum Major for Justice Dinner at Hilton Hotel - Watkins, Howard::::::::: (1988)
?speaking, standing: Les Kimber, Pauline Limber, and Mark Kimber; seated Mayor Dale Doig, and ?